Dark triad personality and public acceptance of homosexuals among Malaysian adults: Interdependent self-construal as a moderator - Wong, Muriel Jie Chee; See, Tong Shin (2024)
Dark Triad traits - narcissism, Machiavellianism and psychopathy, are associated with marginalizing tendencies. However, little research has been done on darker aspects of personality regarding social attitudes in the Malaysian homosexual community. Additionally, interdependent self-construal is the extent of the self based on one’s relationships, group memberships and social roles, which is common in collectivistic culture like Malaysia. Therefore, this study aims to examine the relationship between the Dark Triad and public acceptance of homosexuals among Malaysian adults, while exploring the moderating effect of interdependent self-construal on this relationship. 200 straight, multiracial Malaysians with a mean age of 24.8 ±7.6 were recruited using a non-probability sampling method for an Internet-based survey. Respondents were required to respond to the Homosexuality Attitude Scale, the Self-Construal Scale, and the Short Dark Triad. Among the Dark Triad, narcissism was found to correlate negatively with public acceptance of homosexuals. Those with high narcissism are more likely to be homonegative to preserve in-group dignity and avoid social ostracism. However, interdependent self-construal does not moderate the relationship between the Dark Triad and homosexual acceptance. The emergence of individualism and conflicting self-construals may contribute to this result, which challenges the collectivistic norms that are expressed by interdependent self-construal. The results of this study expanded the Malaysian public acceptance of homosexual literature by introducing interdependent self-construal as a moderator and utilising the Dark Triad instead of the Big Five. It also unveiled the theoretical intricacies of self-construal that are highly relevant in a culturally rich context. This study also pushes for human rights policies in accordance with the sustainable development goals.